Feedlot performance, feed efficiency and carcass traits in Nellore cattle selected for postweaning weight - Lucila Sobrinho, Tatiana [UNESP]; Bonilha, Sarah Figueiredo Martins; Gonçalves, Heraldo César [UNESP]; Castilhos, André Michel de [UNESP]; Magnani, Elaine; Razook, Alexander George; Branco, Renata Helena (Sociedade Brasileira de Zootecnia, 2013)
The objective of this study was to evaluate the correlated responses to selection for growth in feed efficiency and carcass traits of Nellore animals. A total of 121 animals of the Nellore control (NeC) and selection herds were subjected to performance testing and classified regarding residual feed intake (RFI). Sixty-seven of these animals were selected and finished until reaching 4 mm of subcutaneous fat thickness between the 12th and 13th ribs. The animals were slaughtered at a mean age of 541 days and mean live weight of 423 kg for NeS and of 363 kg for NeC, and carcass traits were measured. Animals in NeS presented higher initial and slaughter weights, dry matter intake, hot and cold carcass weight, weight of retail cuts, and carcass yield than NeC animals for the same slaughter age and feedlot time. No significant differences in RFI were observed between herds, showing that the weight gain from selection for growth did not cause changes in the energy efficiency of the animals.
Keywords: beef cattle; carcass yield; meat cuts; selection